Clinically and Microbiologically Derived Azithromycin Susceptibility Breakpoints for Salmonella enterica Serovars Typhi and Paratyphi A - Parry, Christopher M. (Antimicrob Agents Chemother, 2015)
Azithromycin is an effective treatment for uncomplicated infections with Salmonella enterica serovar Typhi and serovar Paratyphi A (enteric fever), but there are no clinically validated MIC and disk zone size interpretative guidelines. We studied individual patient data from three randomized controlled trials (RCTs) of antimicrobial treatment in enteric fever in Vietnam, with azithromycin used in one treatment arm, to determine the relationship between azithromycin treatment response and the azithromycin MIC of the infecting isolate. We additionally compared the azithromycin MIC and the disk susceptibility zone sizes of 1,640 S. Typhi and S. Paratyphi A clinical isolates collected from seven Asian countries. In the RCTs, 214 patients who were treated with azithromycin at a dose of 10 to 20 mg/ml for 5 to 7 days were analyzed. Treatment was successful in 195 of 214 (91%) patients, with no significant difference in response (cure rate, fever clearance time) with MICs ranging from 4 to 16 μg/ml. The proportion of Asian enteric fever isolates with an MIC of ≤16 μg/ml was 1,452/1,460 (99.5%; 95% confidence interval [CI], 98.9 to 99.7) for S. Typhi and 207/240 (86.3%; 95% CI, 81.2 to 90.3) (P < 0.001) for S. Paratyphi A. A zone size of ≥13 mm to a 5-μg azithromycin disk identified S. Typhi isolates with an MIC of ≤16 μg/ml with a sensitivity of 99.7%. An azithromycin MIC of ≤16 μg/ml or disk inhibition zone size of ≥13 mm enabled the detection of susceptible S. Typhi isolates that respond to azithromycin treatment. Further work is needed to define the response to treatment in S. Typhi isolates with an azithromycin MIC of >16 μg/ml and to determine MIC and disk breakpoints for S. Paratyphi A.